Multifocal Diffuse Dermal Angiomatosis: A Reflection of High Cardiovascular Risk - Emmanuelle Diaz; Clélia Vanhaecke; Julia Sanchez; Anne Durlach; Laurence Gusdorf; Manuelle Viguier (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)